Xenofeminism - Hester, Helen 1983- (Theory redux., 2018)
"In an era of accelerating technology and increasing complexity, how should we reimagine the emancipatory potential of feminism? How should gender politics be reconfigured in a world being transformed by automation, globalization and the digital revolution? These questions are addressed in this bold new book by Helen Hester, a founding member of the 'Laboria Cuboniks' collective that developed the acclaimed manifesto 'Xenofeminism: A Politics for Alienation'. Hester develops a three-part definition of xenofeminism grounded in the ideas of technomaterialism, anti-naturalism, and gender abolitionism. She elaborates these ideas in relation to assistive reproductive technologies and interrogates the relationship between reproduction and futurity, while steering clear of a problematic anti-natalism. Finally, she examines what xenofeminist technologies might look like in practice, using the history of one specific device to argue for a future-oriented gender politics that can facilitate alternative models of reproduction. Challenging and iconoclastic, this visionary book is the essential guide to one of the most exciting intellectual trends in contemporary feminism."--